Optimizing Saffron Flowering and Yield as Affected by Vernalization and Corm Size of Crocus Sativus L. - Shah, Syed Qaiser Ali; Ahmad, Masood; Ali, Hamza; Naeem, Ahmad; Raza, Mehdi; Hassan, Asim; Hussain, Sadaf; Jabin, Shahana; Ayaz, Sumbal; Midrar Ullah; Arif Ullah; Qazi, Imran (Indus Journal of Bioscience Research, 2024)
The absence of low temperature treatment leads to slow shoot growth in spring and results in flowering and various physiological disorders. Among several naturally occurring environmental factors, temperature is considered to play a predominant role in controlling proper growth and flowering in geophytes. Most of them require a “cold-warm” sequence to complete their annual cycle. Exposure of corms to vernalization is the most important physiological phenomenon and ecological factor governing variation of the vegetative apex into the reproductive one in saffron. Results findings showed that among different vernalization treatments, minimum days to emergence, highest emergence percentage, number of leaves plant-1, maximum leaf length (cm), number of cormels plant-1 were observed in saffron plants when corms were treated for 16 days vernalization while maximum number of sprouts corm-1, plant height (cm) and cormels weight (g) were recorded in saffron corms treated with 12 days vernalization. Among different corm sizes, minimum days to emergence, maximum emergence percentage, number of sprouts corm-1, average plant height (cm), number of leaves plant-1, leaf length (cm), number of cormels plant-1 and highest cormels weight plant-1 (g) were noticed in larger corm size (11g). It is concluded from the research findings that saffron corms of larger size when treated for 16 days vernalization could give better production.